Comparative evaluation of physiological and biochemical alteration in tomato plants infected by Alternaria alternata in response to Trichoderma viride and Chaetomium globosum application. (August 2021) - Khalil, Mohamed I.I.; Youssef, Sahar A.; Tartoura, Kamel A.; Eldesoky, Abrar A.
Abstract: Tomato is one of the most consumable vegetable crops worldwide. The crop is affected by several pathogens and early blight disease is one of the most deleterious diseases that can severely affect tomato foliage. The current study was carried out to evaluate the effectiveness of the endophytic fungi Trichoderma viride and Chaetomium globosum to manage the early blight disease of tomato and to assess the plant innate defense response to the biocontrol agents application. Results revealed that foliar application of T. viride and C. globosum either alone or in combination reduced disease incidence by 73.3, 37.6, 59.1% respectively while disease severity reached 18.7, 46.4, 37.6% compared to control plants. At the same time, the treatments increased tomato growth significantly both the shoot fresh weight at a rate of 32, 9, 25% and root fresh weight at a rate of 54, 18, 27% of T . viride, C. globosum and the mixture of the two fungi respectively. Consequently, the shoot and root dry weights were increased as compared to control plants. Measurements of physiological and biochemical parameters exhibited a substantial increase in chlorophyll contents (Chl a, Chl b, Total chl) but a decrease in hydrogen peroxide (H2 O2 ), membrane ion leakage, and Malondialdehyde (MDA) levels at 48 and 96 h post treatments. Furthermore, assessment of the antioxidant enzymes superoxide dismutase (SOD) and catalase (CAT) revealed a substantial enhancement of the SOD enzymatic activities reached 3, 1.8, 2.6 folds at day 3 and 5.2, 2.8, 3.8 folds at day 5 post treatments for T. viride, C. globosum and the mixture of the two fungi respectively whereas the increase in CAT activities reached 4.6, 2.3, 2.6 folds at day 3 and 16, 9.5, 9.5 folds at day 5 of the same treatments respectively. Subsequently, it was concluded that the two fungi were able to protect tomato plants against A. alternata via suppression of disease incidence, enhancement of chlorophyll contents, improvement of the plant health and induction of tomato innate defense system. Generally, T. viride was more effective in controlling early blight disease over C. globosum alone or in combination with T. viride . There was no synergistic interaction observed. Highlights: - Endophytes protected tomato plants against early blight Alternaria alternata. - Trichoderma viride and Chaetomium globosum were reduced disease incidence and severity. - Biocontrol agents increased chlorophyll contents and plant growth attributes. - Treatments controlled ROS production and reduced membrane ion leakage and lipid peroxidation. - Antioxidant enzymes superoxide dismutase and catalase increased up to 5.2 and 16 folds post treatments.